A Cross-sectional study on Out-of-Pocket expenditure towards Immunization and its consequences faced by families with under-five Children Residing at one of the Cities of Western India - Desai, Neel B; Solanki, Asha K; Dave, Viral R; Rathod, Vasu G (Indian Journal of Community Health, 2023)
Background: When immunization of under-five children results in Out-of-Pocket Expenditure (OOPE), it affects motivation of parents for vaccination inversely. Objectives: To assess determinants affecting preference for specific/mixed type of health facilities and to estimate out-of-pocket expenditure towards immunization of under-five children. To assess opinion of participants for prevention/decreasing OOPE towards immunization. Methods: A community-based cross-sectional study was conducted at one of zones of Ahmedabad city, selected by simple random sampling. Following technique of “30×7 cluster survey” with necessary house-hold information received from Municipal Corporation, selection of 7 children was pursued from each cluster reaching to sample-size of 210 (30 X 7). Results: Of 211 children included in study, 124(58.77%), 68(32.23%) and 19(9%) had taken immunization services from government, private and mixed variety respectively. Majority of families (110, 88.71%) preferring government healthcare-facility for immunization incurred expenses <5000 INR/child as while in other two groups, all beneficiaries had expensed>5000 INR/child. Conclusions: Determinants like child’s gender, parents’ education, Type of family, Socio-economic status, delivery place of child and occupation of father had statistically significant association with preferred place of vaccination. Fixation of upper ceiling-limit of vaccines which are recommended by pediatricians but not covered in government run program was one of suggestions.